Experimental investigation of the interconnections between turbulent structure and scouring topographic characteristics - Li, Jian; Xu, Naixing; Wang, Hao; Fu, Dabao; Liu, Xiaoxiao; Wu, Wei (Frontiers in Environmental Engineering, 2023)
Complex interactions between turbulence and sediment movement around bridge piers result in bridge damage. However, the scouring mechanism remains ambiguous owing to insufficient quantitative experimental analysis pertaining to scouring topographic characteristics and their relationships with turbulent flow. Hence, an experiment is performed in this study to clarify the relationships between turbulent vortex structures and scour topography. First, we measure the two-dimensional flow fields around a bridge pier using particle image velocimetry systems and then establish a three-dimensional scour topography using the structure-from-motion technique. Subsequently, according to the unified coordinate system, we perform an innovative quantitative analysis of the scouring topography and the distributions of the shear force and horseshoe vortex around the pier. The results show the maximum depth of the scour hole increases linearly with the flow intensity. For a single scouring hole, both the cross-sectional area and volume of the scour hole vary parabolically with the height from the pit bottom. The coupling of the flow and bed topography forms the maximum scour hole via shear stress, and the large streamwise vortices on both sides of the bridge pier result in the formation of long shallow grooves on both sides of the sand dune downstream.